Financial liquidity, financing constraints and financing patterns - Karakoç, Bahadır. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Separating firms into groups based on level of financing constraint proxied by size and stock market trading status, changes in financing patterns are investigated in times of high foreign capital flow and expansionary monetary policy. The study fulfills the need for analyzing the consequences of foreign capital flow at firm level and documenting its significance in addition to assessing the efficacy of contemporary monetary policy. Recent economic conditions significantly facilitated lending process, increasing credit supply and strengthening the access to conventional credit, and resulted in excessive borrowing both in the form of foreign and domestic currency. With such heavy burden of debt, the sector has become dependent on continuance of foreign capital entrance to maintain profitability and liquidity, while facing both exchange rate and the liquidity risks. The more severely a firm was previously challenged by financing limitations, the more it has borrowed once the limitations are removed, contributing to excessive debt burden of the economy in proportion to its previous financing constraints. Furthermore, significant changes in trade credit financing decisions are documented; as their access to bank loans is facilitated they reduced portion of interfirm credit, and increased bank financing and the supply of trade credit to smaller firms. Recent expansion in consumption and corporate sales may have motivated firms to supply more trade credit to promote sales and increase market share. Finally, monetary policy is found to be more effective on conventional credit channels than trade credit.
Keywords: Financial management.